Simulasi Gerbang Tol Menggunakan RFID (Radio Frequency Identification) - Dania Eridani; Yuli Christyono; Imam Santoso (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
RFID technology emerges based on human needs. For example, RFID is used for simulation of toll gate. By using RFID, users can be easily having transaction on toll gate. The purpose of this final project is building an automatic and manual simulation on toll gate using RFID which is connected with computer and LED circuit that is controlled by microcontroller. This system consist of two input gates, Karawang Timur gate and an input without passing any gate, also one output gate, Sadang gate. There will be LED circuit that controlled by microcontroller in each gate to give stop and go sign for every vehicle that passing the toll gate. The program that is built consist of transaction program and program for toll’s employee which contain all transaction data in toll gate, employee’s data, RFID user’s data, the user’s balance, and toll gate’s income. From the experiment result, we can get a conclusion that overall the simulation of this toll gate can work according to the program. The reading maximum distance of this RFID is 2cm. Member card can be used in toll gate when the unique number already save in the toll gate’s data. LED circuit can work correctly according to input that given from 5 RFID tags and the variation of the vehicle’s cost in the transaction process in toll gate. Keyword : RFID reader, toll gate, RFID tag, LED circuit, form.